2020
DOI: 10.1007/s10879-020-09466-4
|View full text |Cite
|
Sign up to set email alerts
|

Containing the Anxieties of Children, Parents and Families from a Distance During the Coronavirus Pandemic

Abstract: The coronavirus pandemic and the move to teletherapy has created uncertainty among both clinicians and patients. As therapists who work with children, we have heard from parents who are desperate for support and advice about how to respond to their children's behavioral changes, as well as those who feel too overwhelmed to continue their children's sessions at the moment and want to take a break from treatment. We have had to rethink the frame in concrete ways, reimagine how to play, and renegotiate parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…8. Psychotherapycognitive-behavioural therapy (CBT) is a first line treatment for anxiety (Bate and Malberg 2020;Fineberg, Van Ameringen et al 2020;Khawam et al 2020;Renjun et al 2020). 9.…”
Section: D)mentioning
confidence: 99%
“…8. Psychotherapycognitive-behavioural therapy (CBT) is a first line treatment for anxiety (Bate and Malberg 2020;Fineberg, Van Ameringen et al 2020;Khawam et al 2020;Renjun et al 2020). 9.…”
Section: D)mentioning
confidence: 99%
“…With the COVID-19 pandemic, families are experiencing financial difficulties, having to work remotely or flexibly; their burden has increased due to homeeducation of children, taking precautions against disease transmission, threats to their own or loved ones' health, reduced social support outside the home, and changes in work roles or routines, as well closed schools and child care centers, and they are facing many problems (Galea et al, 2002;Ones, 2020;Prime, Browne, & Wade, 2020). While this has put an enormous burden on parents to provide care, safety and security, it has resulted in profound changes in family routines and rituals that are often considered natural (Bate & Malberg, 2020;C.H. Liu & Doan, 2020;Y.…”
Section: Introductionmentioning
confidence: 99%
“…In the COVID-19 context, this is proposed to be reflected in a parent's capacity to find meaning in daily moments, connect socially, and a capacity to recognize positive alongside negative aspects of the pandemic (Coyne et al, 2020). In addition, the degree to which a parent considers their child's needs and perspective through adversity is well recognized as a positive parenting construct, including through the COVID-19 pandemic (Bate and Malberg, 2020). Existing research has identified an association between cumulative COVID-19 hardship (job loss, income loss, caregiver burden, and household illness) and both parent and child mental health (Gassman-Pines et al, 2020).…”
Section: Introductionmentioning
confidence: 99%